Involvement of argonaute proteins in gene silencing and activation by RNAs complementary to a non-coding transcript at the progesterone receptor promoter - Chu, Yongjun (Oxford University Press, 2010)
Double-stranded RNAs that are complementary to non-coding transcripts at gene promoters can activate or inhibit gene expression in mammalian cells. Understanding the mechanism for modulating gene expression by promoter-targeted antigene RNAs (agRNAs) will require identification of the proteins involved in recognition. Previous reports have implicated argonaute (AGO) proteins, but identifications have differed with involvement of AGO1, AGO2, or both AGO1 and AGO2 being reported by different studies. The roles of AGO3 and AGO4 have not been investigated. Here, we examine the role of AGO 1–4 in gene silencing and activation of the progesterone receptor (PR) gene. Expression of AGO2 is necessary for efficient gene silencing or activation and AGO2 is recruited to the non-coding transcript that overlaps the promoter during both gene silencing and activation. Expression of AGO1, AGO3 and AGO4 are not necessary for gene silencing or activation nor are AGO1, AGO3, or AGO4 recruited to the target non-coding transcript during gene activation. These data indicate that AGO2 is the primary AGO variant involved in modulating expression of PR by agRNAs.